ANALYSIS OF FACTORS INFLUENCING TOKOPEDIA BRAND AWARENESS - Supriyatin SY (Jurnal Multidisiplin Sahombu, 2023)
The world of business is going through a period of fast development. All human needs and desires are always evolving and growing, and as a result, businesses are under increasing pressure to be able to keep up with changes in cultural norms as well as advancements in information and communication technologies. One of these types of activities is shopping done online through mobile applications, specifically the e-commerce portal known as Tokopedia. This study aims to assess the simultaneous and partial empirical effects of advertisements, slogans, brand ambassadors, and electronic word of mouth on Tokopedia's brand awareness. This type of research is known as explanatory research, and its methodology is quantitative. In this study, the author used a survey as the method of investigation. According to the results of this study, there is no correlation between advertising and brand recognition. However, there is a substantial correlation between taglines and brand recognition, a significant correlation between brand ambassadors and brand recognition, and a significant effect between electronic word of mouth and brand recognition.